2020
DOI: 10.1007/s41465-020-00202-3
|View full text |Cite
|
Sign up to set email alerts
|

Is Training with the N-Back Task More Effective Than with Other Tasks? N-Back vs. Dichotic Listening vs. Simple Listening

Abstract: Cognitive training most commonly uses computerized tasks that stimulate simultaneous cognitive processing in two modalities, such as a dual n-back task with visual and auditive stimuli, or on two receptive channels, such as a listening task with dichotically presented stimuli. The present study was designed to compare a dual n-back task and a dichotic listening (DL) task with an active control condition (a simple listening task) and a no-training control condition for their impact on cognitive performance, dai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 87 publications
(108 reference statements)
0
3
0
Order By: Relevance
“…Fourth, although there are no head-to-head comparisons available, there is some evidence to suggest that tests for executive functions (e.g., WCST) and decision making (e.g., IGT) may be more susceptible to practice effects than the tests for working memory (e.g., verbal and visual N-back tests). [ 25 29 ] Out of the five parameters measured in the WCST, only one (perseverative error) showed a significant change over time. Had practice effect been the most likely explanation for this improvement, we should have observed changes in other parameters as well.…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, although there are no head-to-head comparisons available, there is some evidence to suggest that tests for executive functions (e.g., WCST) and decision making (e.g., IGT) may be more susceptible to practice effects than the tests for working memory (e.g., verbal and visual N-back tests). [ 25 29 ] Out of the five parameters measured in the WCST, only one (perseverative error) showed a significant change over time. Had practice effect been the most likely explanation for this improvement, we should have observed changes in other parameters as well.…”
Section: Discussionmentioning
confidence: 99%
“…This result is difficult to interpret, especially since the n-back task was one of the training tasks in the CT. Previous research mostly showed positive effects of CT on n-back related tasks ( Jaeggi et al, 2010 ; Studer-Luethi and Meier, 2020 ). However, after the CT group received the MMI, they significantly improved their performance compared to the MMI group.…”
Section: Discussionmentioning
confidence: 99%
“…This speaks to one of the most contentious issues in the cognitive training literature; that is, whether training on cognitive tasks can lead to generalized improvements in cognition. While some authors have suggested that training on one cognitive task leads to improvements on unrelated tasks (Au et al, 2015; Brem et al, 2018; De Lillo, Brunsdon, Bradford, Gasking, & Ferguson, 2021; Flegal, Ragland, & Ranganath, 2019; Jaeggi, Buschkuehl, Jonides, & Perrig, 2008; Kattner, 2021; Li et al, 2021; Olfers & Band, 2018; Studer‐Luethi & Meier, 2020), a considerable number of studies have failed to show such effects (Owen et al, 2010; Stojanoski et al, 2020; Stojanoski, Lyons, Pearce, & Owen, 2018). Indeed, while the holy grail of the cognitive training literature is so‐called “far transfer” (i.e., where training on one task improves performance on a completely unrelated second task), many studies have failed to even demonstrate “near transfer” (i.e., when training on one task improves performance on a similar, cognitively related second task) (Simons et al, 2016).…”
Section: Introductionmentioning
confidence: 99%